Technological change and labor markets : productivity, job polarization, and inequality - Rodríguez Pérez, Reyna Elizabeth [Herausgeber]; Meza González, Liliana [Herausgeber] (Routledge, 2025)
"In developed countries like the US, Germany and the UK it has been observed that workers who perform non-routine activities, either cognitive or manual, have benefited in terms of employment and income, while those performing routinary tasks have seen their job prospects and wages decline. This has led to a polarization of the labor markets and to a decrease in certain measures of inequality. This phenomenon has been attributed to task-biased technological change (TBTC), which differs from the skilled biased technological change in the fact that not only highly skilled workers have benefited from technology advancement. This book presents evidence of how digitalization and task-biased technological change are affecting the labor markets of different regions of the world and examines the factors that cause this inequality among nations. It examines recent issues around the effect of task-biased technological change on labor markets and the economy in general, with a comparison of different countries in Central and Eastern Europe, North America, and Latin America, as well as in other regions of the world. The incorporation of the abovementioned regions presents relevant particularities for the subject matter addressed in the book. The book also considers questions such as how labor market effects differ by gender and what the impact of digital skills on employment, inequalities and public policies might be. In so doing, it identifies the advances, opportunities, and changes that have taken place, while also making public policy proposals. The main market for the book is the global community of graduate students and researchers in the field of economics and, specifically, in the study of labor markets." (Publisher, BIBB-Doku)
E-Book für BIBB-Mitarbeitende über die Bibliothek erhältlich.
Keywords: G 2.2.1 Technologisierung; G 1.2 Arbeitsmarkt; G 1.2.2 Beschäftigungs- und Arbeitsverhältnisse; I 2.2 Europa; I 2.2.2 Osteuropa; I 2.3.2 Nordamerika; I 2.3.3 Lateinamerika; 370; Technischer Fortschritt; Digitalisierung; Arbeitsmarkt; Beschäftigungseffekte; Einkommensverteilung; Lohnstruktur; Qualifikation; Arbeitsproduktivität; Internationaler Vergleich; Mitteleuropa; Osteuropa; Europäische Union; Spanien; Bundesrepublik Deutschland; USA; Nordamerika; Brasilien; Mexiko; Lateinamerika